Schools and Communities of Norm-awareness - Gabriella Pusztai (Religions, 2011)
The relationship between religiosity and educational attainment is an important question in the sociology of religion literature. It is widely contested whether the natural outgrowth of the spreading rational worldview and the increase of educated people can account for the decline of religious adherence. Is there any other explanation for the different opportunities of religious and non-religious societal groups to obtaining the highest educational level? After the political transformation in Central and Eastern Europe, one of the most important challenges of restructuring the educational system was how different cultural groups would be able to infuse their own spirituality into their children's education after the domination of the totalitarian ideology. The Hungarian case is unique because of the mixed confessional landscape, the populous Hungarian minority outside the border, the alternating hard and soft periods of religious harassment. Recently, more than half of the Hungarian population can be described as religious in their own way, one sixth strongly affiliated with churches, and another sixth are atheists. However, several studies showed that basic indicators of social status were very strongly and negatively interrelated with religiosity. It turned out that preferred educational views, values, approaches and priorities regarding the norms at schools differ very sharply according to the religious views, and belonging to a religious network significantly supports educational careers. This paper is a comprehensive review of research on the educational functions of denominational schools and religious communities in contemporary Hungary.